Splanchnic Venous Compression Enhances the Effects of ß‐Blockade in the Treatment of Postural Tachycardia Syndrome. Issue 14 (21st July 2020) - Smith, Emily C.; Diedrich, André; Raj, Satish R.; Gamboa, Alfredo; Shibao, Cyndya A.; Black, Bonnie K.; Peltier, Amanda; Paranjape, Sachin Y.; Biaggioni, Italo; Okamoto, Luis E.
Abstract : Background: Splanchnic venous pooling induced by upright posture triggers a compensatory increase in heart rate (HR), a response that is exaggerated in patients with postural tachycardia syndrome. To assess whether abdominal compression attenuates orthostatic tachycardia and improves symptoms, 18 postural tachycardia syndrome patients (32±2 years) were randomized to receive either abdominal compression (40 mm Hg applied with an inflatable binder ≈2 minutes before standing) or propranolol (20 mg) in a placebo‐controlled, crossover study. Methods and Results: Systolic blood pressure, HR, and symptoms were assessed while seated and standing, before and 2 hours postdrug. As expected, propranolol decreased standing HR compared with placebo (81±2 versus 98±4 beats per minute; P <0.001) and was associated with lower standing systolic blood pressure (93±2 versus 100±2 mm Hg for placebo; P =0.002). Compression had no effect on standing HR (96±4 beats per minute) but increased standing systolic blood pressure compared with placebo and propranolol (106±2 mm Hg; P <0.01). Neither propranolol nor compression improved symptoms compared with placebo. In 16 patients we compared the combination of abdominal compression and propranolol with propranolol alone. The combination had no additional effect on standing HR (81±2 beats per minute for both interventions) but prevented the decrease in standing systolic blood pressure produced by propranolol (98±2 versus 93±2 mm Hg for propranolol; P =0.029), and significantly improved total symptom burden (−6±2 versus −1±2 for propranolol; P =0.041). Conclusions: Splanchnic venous compression alone did not improve HR or symptoms but prevented the blood pressure decrease produced by propranolol. The combination was more effective in improving symptoms than either alone. Splanchnic venous compression can be a useful adjuvant therapy to propranolol in postural tachycardia syndrome. Registration: URL: https://www.clini​caltr​ials.gov ; Unique identifier: NCT00262470.